Correction: Efficiently increasing the radiative rate of TADF material with metal coordination. Issue 84 (11th October 2022) - Cai, Xian-Bao; Liang, Dong; Yang, Mingxue; Wu, Xiao-Yuan; Lu, Can-Zhong; Yu, Rongmin
Abstract : Correction for 'Efficiently increasing the radiative rate of TADF material with metal coordination' by Xian-Bao Cai et al., Chem. Commun., 2022, 58, 8970–8973, ; https://doi.org/10.1039/D2CC02930H .